2014
DOI: 10.3844/ajavsp.2014.239.244
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Status for Selected Pig Breeds

Abstract: Changes which are constantly brought by the transformation of our agriculture, as well as the effort to be involved in the EU market economy and change priorities in various areas of our economy. They can be summarized in the quality, productive health and economy. Blood count does not only change in pigs with age, but it also depends on the method of pig housing, feed and thermal regime. Changes in the haematological status of the organism eventually affects the quality of meat. This study focuses on the hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The linear relationship between red blood cell parameters and body weight can be explained by the increasing blood volume and the amount of hemoglobin and hematocrit in the body (Crichton, 2006). Kotosová et al (2014) found no significant differences in RBC values measured in different seasons. Hemoglobin and hematocrit are indirect indicators of the iron status of piglets.…”
Section: ____________________________________________________________mentioning
confidence: 60%
“…The linear relationship between red blood cell parameters and body weight can be explained by the increasing blood volume and the amount of hemoglobin and hematocrit in the body (Crichton, 2006). Kotosová et al (2014) found no significant differences in RBC values measured in different seasons. Hemoglobin and hematocrit are indirect indicators of the iron status of piglets.…”
Section: ____________________________________________________________mentioning
confidence: 60%
“…Changes in blood profiles can determine health status in animal bodies [ 25 , 28 ]. The current study demonstrated that the AST concentration was unaffected by dietary treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Hematologic and biochemical values can vary dependent on presence of inflammation and infection [5,20,24,26,27,30]. Change of blood parameters is consequence of negative factors influence like heath stress and transport [3,18]. Biochemical parameters in blood indicate metabolic status of pigs and they change under the influence of nutrition and breed [1].…”
Section: Introductionmentioning
confidence: 99%